Poor banished children of Eve : woman as evil in the Hebrew Bible - Yee, Gale A., 1949- (Minneapolis, MN : Fortress Press, 2003)
Analyzes four biblical passages (Genesis 2-3, Hosea 1-3, Ezekiel 23, and Proverbs 7) in which a woman is the source or symbol of sin.
Includes bibliographical references (p. 233-269) and indexes.
Keywords: Bible. -- Criticism, interpretation, etc; Bible. -- Feminist criticism; Women in the Bible